An ensemble-forecasting model for airborne grass pollen at three climatically distinct sites - Maria P. Plaza; Jose Oteros; Vivien Leier-Wirtz; Athanasios Charalampopoulos; Carmen Galán; Caroline Holzmann; Franziska Kolek; Despoina Vokou; Claudia Traidl-Hoffmann; Stefanie Gilles; Athanasios Damialis (Environmental Research, 2026)

Diversity and abundance of airborne pollen and fungal spores at different heights, outdoors and indoors - Athanasios Charalampopoulos; Athanasios Damialis; Danai-Eleni Michailidou; Despoina Vokou (Urban Ecosystems, 2026)

Recommended terminology for aerobiological studies: automatic and real-time monitoring methods - Fiona Tummon; Katharina Bastl; Maximilian Bastl; Paul J. Beggs; Jordina Belmonte; Nicolas Bruffaerts; Athanasios Charalampopoulos; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; Sophie Erb; et al. (Aerobiologia, 2025)

Topical collection: aerobiology and planetary health - Athanasios Damialis; Łukasz Grewling; Matt Smith (Aerobiologia, 2025)

A multi-scale analysis of airborne Alternaria spore dispersal: influence of meteorology, land cover and air pollution - Maria P. Plaza; Jose Oteros; Vivien Leier-Wirtz; Franziska Kolek; Annette Menzel; Jeroen T.M. Buters; Claudia Traidl-Hoffmann; Athanasios Damialis (Agricultural and Forest Meteorology, 2025)

Air quality in the era of climate change: Bioaerosols, multi-exposures, and the emerging threats of respiratory allergies and infectious diseases - Athanasios Damialis; Stefanie Gilles (Current Opinion in Environmental Science & Health, 2025)

Plants on the ground, pollen in the air: how much do they match? - Despoina Vokou; Athanasios Charalampopoulos; Maria Lazarina; Olga Tsingani-Papanikolaou; Kleopatra Leontidou; Despoina Paschalidou; Athanasios Damialis; Effie Hanlidou (Aerobiologia, 2024)

Continental-scale evaluation of downy birch pollen production: Estimating the impacts of global change - Surendra Ranpal; Susanne von Bargen; Stefanie Gilles; Daria Luschkova³; Maria Landgraf; Pawel Bogawski; Claudia Traidl-Hoffmann; Carmen Büttner; Athanasios Damialis; Markus Fritsch; Susanne Jochner-Oette (Environmental Research, 2024)

The role of automatic pollen and fungal spore monitoring across major end-user domains - Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; Nicolas Bruffaerts; Jeroen Buters; Paloma Cariñanos; Sevcan Celenk; Marie Choël; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; et al. (Aerobiologia, 2024)
The advent of automatic pollen and fungal spore monitoring over the past few years has brought about a paradigm change. The provision of real-time information at high temporal resolution opens the door to a wide range of improvements in terms of the products and services made available to a widening range of end-users and stakeholders. As technology and methods mature, it is essential to properly quantify the impact automatic monitoring has on the different end-user domains to better understand the real long-term benefits to society. In this paper, we focus the main domains where such impacts are expected, using Europe as a basis to provide qualitative estimates and to describe research needs to better quantify impacts in future. This will, in part, also serve to justify further investment and help to expand monitoring networks.

Co-exposure to highly allergenic airborne pollen and fungal spores in Europe - Dorota Myszkowska; Paweł Bogawski; Katarzyna Piotrowicz; Beata Bosiacka; Agnieszka Grinn-Gofroń; Uwe E. Berger; Maira Bonini; Valentina Ceriotti; Athanasios Charalampopoulos; Carmen Galán; Björn Gedda; Nicoleta Ianovici; et al. (Science of The Total Environment, 2023)

A temporally and spatially explicit, data-driven estimation of airborne ragweed pollen concentrations across Europe - László Makra; István Matyasovszky; Gábor Tusnády; Lewis H. Ziska; Jeremy J. Hess; László G. Nyúl; Daniel S. Chapman; Luca Coviello; Andrea Gobbi; Giuseppe Jurman; Cesare Furlanello; Mauro Brunato; et al. (Science of The Total Environment, 2023)

Airborne pollen grain detection from partially labelled data utilising semi-supervised learning - Benjamin Jin; Manuel Milling; Maria Pilar Plaza; Jens O. Brunner; Claudia Traidl-Hoffmann; Björn W. Schuller; Athanasios Damialis (Science of The Total Environment, 2023)

Pollen long-distance transport associated with symptoms in pollen allergics on the German Alps: An old story with a new ending? - Daniela Bayr; Maria P. Plaza; Stefanie Gilles; Franziska Kolek; Vivien Leier-Wirtz; Claudia Traidl-Hoffmann; Athanasios Damialis (Science of The Total Environment, 2023)

Betula pendula trees infected by birch idaeovirus and cherry leaf roll virus: Impacts of urbanisation and NO2 levels - Stefanie Gilles; Meike Meinzer; Maria Landgraf; Franziska Kolek; Susanne von Bargen; Kaja Pack; Athanasios Charalampopoulos; Surendra Ranpal; Daria Luschkova; Claudia Traidl-Hoffmann; Susanne Jochner-Oette; Athanasios Damialis; et al. (Environmental Pollution, 2023)

Pollen production of downy birch (Betula pubescens Ehrh.) along an altitudinal gradient in the European Alps - Surendra Ranpal; Susanne von Bargen; Stefanie Gilles; Daria Luschkova; Maria Landgraf; Claudia Traidl-Hoffmann; Carmen Büttner; Athanasios Damialis; Susanne Jochner-Oette (International Journal of Biometeorology, 2023)
High-altitude environments are highly susceptible to the effects of climate change. Thus, it is crucial to examine and understand the behaviour of specific plant traits along altitudinal gradients, which offer a real-life laboratory for analysing future impacts of climate change. The available information on how pollen production varies at different altitudes in mountainous areas is limited. In this study, we investigated pollen production of 17 birch ( Betula pubescens Ehrh.) individuals along an altitudinal gradient in the European Alps. We sampled catkins at nine locations in the years 2020–2021 and monitored air temperatures. We investigated how birch pollen, flowers and inflorescences are produced in relation to thermal factors at various elevations. We found that mean pollen production of Betula pubescens Ehrh. varied between 0.4 and 8.3 million pollen grains per catkin. We did not observe any significant relationships between the studied reproductive metrics and altitude. However, minimum temperature of the previous summer was found to be significantly correlated to pollen ( r s = 0.504, p = 0.039), flower ( r s = 0.613, p = 0.009) and catkin ( r s = 0.642, p = 0.005) production per volume unit of crown. Therefore, we suggest that temperature variability even at such small scales is very important for studying the response related to pollen production.

Spatiotemporal assessment of aeromycoflora under differing urban green space, sampling height, and meteorological regimes: the atmospheric fungiscape of Thessaloniki, Greece - Athanasios Charalampopoulos; Athanasios Damialis; Despoina Vokou (International Journal of Biometeorology, 2022)

Five ways to define a pollen season: exploring congruence and disparity in its attributes and their long-term trends - Thomas Tasioulis; Kostas Karatzas; Athanasios Charalampopoulos; Athanasios Damialis; Despoina Vokou (Aerobiologia, 2022)

Threshold values of grass pollen (Poaceae) concentrations and increase in emergency department visits, hospital admissions, drug consumption and allergic symptoms in patients with allergic rhinitis: a systematic review - Jana Becker; Nadine Steckling-Muschack; Isabella Mittermeier; Karl-Christian Bergmann; Stephan Böse-O’Reilly; Jeroen Buters; Athanasios Damialis; Katharina Heigl; Joachim Heinrich; Michael Kabesch; Hanna Mertes; Dennis Nowak; et al. (Aerobiologia, 2021)

Effects of future climate change on birch abundance and their pollen load - Jesús Rojo; Jose Oteros; Antonio Picornell; José M. Maya‐Manzano; Athanasios Damialis; Katrin Zink; Matthias Werchan; Barbora Werchan; Matt Smith; Annette Menzel; Sabine Timpf; Claudia Traidl‐Hoffmann; et al. (Global Change Biology, 2021)
Climate change impacts on the structure and function of ecosystems will worsen public health issues like allergic diseases. Birch trees ( Betula spp.) are important sources of aeroallergens in Central and Northern Europe. Birches are vulnerable to climate change as these trees are sensitive to increased temperatures and summer droughts. This study aims to examine the effect of climate change on airborne birch pollen concentrations in Central Europe using Bavaria in Southern Germany as a case study. Pollen data from 28 monitoring stations in Bavaria were used in this study, with time series of up 30 years long. An integrative approach was used to model airborne birch pollen concentrations taking into account drivers influencing birch tree abundance and birch pollen production and projections made according to different climate change and socioeconomic scenarios. Birch tree abundance is projected to decrease in parts of Bavaria at different rates, depending on the climate scenario, particularly in current centres of the species distribution. Climate change is expected to result in initial increases in pollen load but, due to the reduction in birch trees, the amount of airborne birch pollen will decrease at lower altitudes. Conversely, higher altitude areas will experience expansions in birch tree distribution and subsequent increases in airborne birch pollen in the future. Even considering restrictions for migration rates, increases in pollen load are likely in Southwestern areas, where positive trends have already been detected during the last three decades. Integrating models for the distribution and abundance of pollen sources and the drivers that control birch pollen production allowed us to model airborne birch pollen concentrations in the future. The magnitude of changes depends on location and climate change scenario.

A systematic review of threshold values of pollen concentrations for symptoms of allergy - Nadine Steckling-Muschack; Hanna Mertes; Isabella Mittermeier; Paul Schutzmeier; Jana Becker; Karl-Christian Bergmann; Stephan Böse-O′Reilly; Jeroen Buters; Athanasios Damialis; Joachim Heinrich; Michael Kabesch; Dennis Nowak; et al. (Aerobiologia, 2021)

Forecasting Betula and Poaceae airborne pollen concentrations on a 3-hourly resolution in Augsburg, Germany: toward automatically generated, real-time predictions - Anna Muzalyova; Jens O. Brunner; Claudia Traidl-Hoffmann; Athanasios Damialis (Aerobiologia, 2021)
Airborne allergenic pollen impact the health of a great part of the global population. Under climate change conditions, the abundance of airborne pollen has been rising dramatically and so is the effect on sensitized individuals. The first line of allergy management is allergen avoidance, which, to date, is by rule achieved via forecasting of daily pollen concentrations. The aim of this study was to elaborate on 3-hourly predictive models, one of the very few to the best of our knowledge, attempting to forecast pollen concentration based on near-real-time automatic pollen measurements. The study was conducted in Augsburg, Germany, during four years (2016–2019) focusing on Betula and Poaceae pollen, the most abundant and allergenic in temperate climates. ARIMA and dynamic regression models were employed, as well as machine learning techniques, viz. artificial neural networks and neural network autoregression models. Air temperature, relative humidity, precipitation, air pressure, sunshine duration, diffuse radiation, and wind speed were additionally considered for the development of the models. It was found that air temperature and precipitation were the most significant variables for the prediction of airborne pollen concentrations. At such fine temporal resolution, our forecasting models performed well showing their ability to explain most of the variability of pollen concentrations for both taxa. However, predictive power of Betula forecasting model was higher achieving R 2 up to 0.62, whereas Poaceae up to 0.55. Neural autoregression was superior in forecasting Betula pollen concentrations, whereas, for Poaceae, seasonal ARIMA performed best. The good performance of seasonal ARIMA in describing variability of pollen concentrations of both examined taxa suggests an important role of plants’ phenology in observed pollen abundance. The present study provides novel insight on per-hour forecasts to be used in real-time mobile apps by pollen allergic patients. Despite the huge need for real-time, short-term predictions for everyday clinical practice, extreme weather events, like in the year 2019 in our case, still comprise an obstacle toward highly performing forecasts at such fine timescales, highlighting that there is still a way to go to this direction.

Pollen season identification for three pollen taxa in Thessaloniki, Greece: a 30-year retrospective analysis - Kostas Karatzas; Aggelos Tsiamis; Athanasios Charalampopoulos; Athanasios Damialis; Despoina Vokou (Aerobiologia, 2019)

Pollen allergy and health behavior: patients trivializing their disease - Anna Muzalyova; Jens O. Brunner; Claudia Traidl-Hoffmann; Athanasios Damialis (Aerobiologia, 2019)

Fungi in a changing world: growth rates will be elevated, but spore production may decrease in future climates - Athanasios Damialis; Aqilah B. Mohammad; John M. Halley; Alan C. Gange (International Journal of Biometeorology, 2015)

Ten years of co-management in Greek protected areas: an evaluation - Despoina Vokou; Panayiotis G. Dimitrakopoulos; Nikoleta Jones; Athanasios Damialis; Nikos Monokrousos; John D. Pantis; Antonios D. Mazaris (Biodiversity and Conservation, 2014)

Pollen production and circulation patterns along an elevation gradient in Mt Olympos (Greece) National Park - Athanasios Charalampopoulos; Athanasios Damialis; Ioannis Tsiripidis; Theodoros Mavrommatis; John M. Halley; Despoina Vokou (Aerobiologia, 2013)

Effects of environmental factors on pollen production in anemophilous woody species - Athanasios Damialis; Christina Fotiou; John M. Halley; Despoina Vokou (Trees, 2011)

Parietaria judaica flowering phenology, pollen production, viability and atmospheric circulation, and expansive ability in the urban environment: impacts of environmental factors - Christina Fotiou; Athanasios Damialis; Nikolaos Krigas; John M. Halley; Despoina Vokou (International Journal of Biometeorology, 2011)

Transport of airborne pollen into the city of Thessaloniki: the effects of wind direction, speed and persistence - Athanasios Damialis; Dimitrios Gioulekas; Chariklia Lazopoulou; Christos Balafoutis; Despina Vokou (International Journal of Biometeorology, 2005)

Fifteen years' record of airborne allergenic pollen and meteorological parameters in Thessaloniki, Greece - Dimitrios Gioulekas; Christos Balafoutis; Athanasios Damialis; Despoina Papakosta; George Gioulekas; Dimitrios Patakas (International Journal of Biometeorology, 2004)